2019
DOI: 10.1016/j.biortech.2019.121495
|View full text |Cite
|
Sign up to set email alerts
|

Steam gasification of land, coastal zone and marine biomass by thermal gravimetric analyzer and a free-fall tubular gasifier: Biochars reactivity and hydrogen-rich syngas production

Abstract: The steam gasification properties and kinetics, products distribution and syngas composition derived from land, coastal zone and marine biomass have been studied by TGA and free-fall tubular gasifier. Volume model, shrinking core model and random pore model were applied to describe the reaction kinetics. The influence of temperature and fuel types on steam gasification in a free-fall tubular gasifier were clarified simultaneously. Results showed that gasification reactivity of reed (Re) and Sargassum horneri (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The seawater Spirulina chars was provided by the pilot plant designed by our groups. Please refer to the literature for specific methods [21], and on this basis getting improved. The bio-chars were prepared by devolatilizing the raw materials in free-fall tubular gasifier under a flowing nitrogen atmosphere (6 L/min) at 800 C. This is a most critical step connecting microalgae pyrolysis and gasification, and the bio-char are raw material on industrialization utilization for the preparation of syngas.…”
Section: Seawater Spirulina Char Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The seawater Spirulina chars was provided by the pilot plant designed by our groups. Please refer to the literature for specific methods [21], and on this basis getting improved. The bio-chars were prepared by devolatilizing the raw materials in free-fall tubular gasifier under a flowing nitrogen atmosphere (6 L/min) at 800 C. This is a most critical step connecting microalgae pyrolysis and gasification, and the bio-char are raw material on industrialization utilization for the preparation of syngas.…”
Section: Seawater Spirulina Char Samples Preparationmentioning
confidence: 99%
“…Compared with direct combustion, it has the advantages of stable combustion, high thermal efficiency, low pollution, especially low PM2.5 index [20]. Currently, the research on the gasification technique mainly focuses on isothermal gasification [21]. The gasification temperature and gasification agent are two important factors in the isothermal gasification process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sargassum usually has a low hydrogen content; hence, its use as a fuel precursor can be limited [16]. Li et al [17] gasified Sargassum horneri biochar and found that hydrogen-rich syngas was produced, attributed to its high ash content; it was noted, however, that the high ash content might be related to the algae-growing environment. Hence, it might be different for different cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the endothermic nature of the steam gasification reaction as a whole can operate the reactor more precisely so that important activation energy is provided. The method required for heat input must use steam and air mixtures as gasification agents which can lead to losses from air gasification [36][37][38].…”
Section: Introductionmentioning
confidence: 99%